REQUIREMENTS FOR CREATING VISUALIZATION FOR TRAINING PUPILS - Житєньова, Н. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The author highlighted the requirements for the creation of pedagogically effective digital visual didactic tools intended for use in the school educational process. This requirements contains psychological that include compression, simplicity, emotionality, structure and integrity of the presentation of visual content; pedagogical requirements, in accordance with the contingent of students, consistency with the pedagogical scenario and the use of visual anchors; ergonomic requirements that provide for comfort, harmony, associativity and unification of visual elements; aesthetic requirements based on the consideration of color solutions, the establishment of typographic accents, the use of stylistic unity, prioritization and combining all the elements into a composition